2020
DOI: 10.1371/journal.pone.0238977
|View full text |Cite
|
Sign up to set email alerts
|

Results of the 3 Pillars Study (3PS), a relationship-based programme targeting parent-child interactions, healthy lifestyle behaviours, and the home environment in parents of preschool-aged children: A pilot randomised controlled trial

Abstract: Background Early childhood is a critical period for the development of obesity, with new approaches to prevent obesity in this age group needed. We designed and piloted the 3 Pillars Study (3PS), a healthy lifestyle programme informed by attachment theory for parents of preschool-aged children. Methods A 2-arm, randomised controlled pilot study was conducted to assess the effectiveness of 3PS, a 6-week programme involving a half-day workshop plus 6-week access to a study website. The programme was designed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 63 publications
0
33
0
1
Order By: Relevance
“…The primary analysis found that sleep interventions were associated with 10.5 minutes (95% CI, 5.6-15.4; P < .001) longer nocturnal sleep duration compared with the control condition. Figure 2 shows the primary meta-analysis forest plot, with quality assessments . There was marked heterogeneity across study estimates ( I 2 = 87.2%).…”
Section: Resultsmentioning
confidence: 99%
“…The primary analysis found that sleep interventions were associated with 10.5 minutes (95% CI, 5.6-15.4; P < .001) longer nocturnal sleep duration compared with the control condition. Figure 2 shows the primary meta-analysis forest plot, with quality assessments . There was marked heterogeneity across study estimates ( I 2 = 87.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating daily routines and planning have produced promising results for improving mothers’ physical activity and sleep, as found in a physical activity planning intervention which resulted in additional parent physical activity 23 and child physical activity (ages = 6–12 years). 24 Another intervention in 54 parent–child dyads (ages = 2–5 years) that specifically targeted home routines resulted in lower household chaos and more child sleep, 25 which may be promising for also facilitating maternal sleep. Still, programs should be pragmatic so participation does not add to the mother’s current stress.…”
Section: Discussionmentioning
confidence: 99%
“…Families shape health at an individual level by not only influencing wellbeing at a genetic level, but at an environmental level [ 56 , 57 ], with members often demonstrating shared behaviours including diet, physical activity and smoking. Despite this, there have been limited studies with households and families as the target unit of randomisation, with most household-level trials in the literature focusing on investigating behavioural change environments for children [ 12 , 58 , 59 ]. By intervening at household level, it is hypothesised that lifestyle adaptations will be better sustained by changing the overall routine and habitual patterns of families.…”
Section: Discussionmentioning
confidence: 99%